Biogeochemical formation of calyx-shaped carbonate crystal fans in the subsurface of the Early Triassic seafloor - Heindel, Katrin; Richoz, Sylvain; Birgel, Daniel; Brandner, Rainer; Klügel, Andreas; Krystyn, Leopold; Baud, Aymon; Horacek, Micha; Mohtat, Tayebeh; Peckmann, Joern (Gondwana Research, 2015)
Keywords: Diagenetic carbonate; End-Permian extinction; Lipid biomarkers; Rare earth elements; Subseafloor

Cryptic biostalactites in a submerged karst cave of the Belize Barrier Reef revisited: Pendant bioconstructions cemented by microbial micrite - Gischler, Eberhard; Heindel, Katrin; Birgel, Daniel; Brunner, Benjamin; Reitner, Joachim; Peckmann, Jörn (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Microbial carbonates are important components of postglacial tropical coral reef frameworks. Curious calcium carbonate protrusions in a submarine karst cave in the Belize Barrier Reef platform were initially interpreted as being largely the product of physicochemical precipitation around a meshwork of serpulid tubes. New petrographical, mineralogical, geochronological, and inorganic and organic geochemical data suggest that sulfate-reducing bacteria played a substantial role in carbonate formation, just as in cryptic settings of other modern, tropical coralgal reefs. The bacterial involvement in carbonate authigenesis is indicated by the content and isotopic composition of carbonate-associated sulfate, the presence of non-isoprenoidal sn-1-mono-O-alkyl glycerol monoethers (MAGEs) and terminally-branched fatty acids, and the observation that the majority of molecular fossils assigned to sulfate-reducing bacteria are tightly associated with the carbonate mineral lattice. The carbonate protrusions that were formerly named pseudostalactites, are termed biostalactites here to underline the significance of biological activity during carbonate formation. The Belize biostalactites are composed of four carbonate phases including serpulid tubes, lithified sediment, and microbial carbonate, as well as unconsolidated sediment usually found in macroborings of bivalve molluscs. Lithified sediment and microbial carbonate are fine-grained with clotted, mottled, and peloidal textures. While serpulid tubes are aragonitic, lithified sediment and microbial carbonates are mixtures of high-magnesium calcite and aragonite. Magnesium-calcite content increases with increasing consolidation. Lithified sediment and microbial carbonate are interpreted as fine, biodetrital sediment that was subsequently cemented by authigenic micrite. Scalenohedral high-magnesium calcite and acicular aragonite cements played a subordinate role in cementation. Carbon and oxygen stable isotope ratios of lithified sediment and microbial carbonate exhibit similar ranges as modern reefal microbialites. Our study exemplifies that heterotrophic bacteria can be a crucial agent that contributes to the formation of carbonate build-ups by cementing skeletal frameworks in cryptic environments.
UnivIS-Import:2017-12-18:Pub.2017.nat.dgeo.IGM.LP.crypti
Keywords: Carbonate; Holocene; Microbialite; Reef; Sulfate reduction

Formation of deglacial microbialites in coral reefs off Tahiti (IODP 310) involving sulfate-reducing bacteria - Heindel, Katrin; Birgel, Daniel; Peckmann, Joern; Kuhnert, Henning; Westphal, Hildegard (Palaios, 2010)
Keywords: coral reef; LA-ICP-MS; last sea-level rise; lipid biomarker; organomineralization

Genesis of microbialites as contemporaneous framework components of deglacial coral reefs, Tahiti (IODP 310) - Westphal, Hildegard; Heindel, Katrin; Brandano, Marco; Peckmann, Joern (Facies, 2010)
Keywords: IODP 310; Microbialites; Nutrients; Reef development; Tahiti

Microbioerosion in Tahitian reefs: A record of environmental change during the last deglacial sea-level rise (IODP 310) - Heindel, Katrin; Wisshak, Max; Westphal, Hildegard (Lethaia, 2008)
The main motivation for Integrated Ocean Drilling Program Expedition 310 to the Tahitian Archipelago was the assumption that the last deglacial sea-level rise is precisely recorded in the coral reefs of this far-field site. The Tahitian deglacial succession typically consists of coral framework subsequently encrusted by coralline algae and microbialites. The high abundance of microbialites is uncommon for shallow-water coral reefs, and the environmental conditions favouring their development are still poorly understood. Microbioerosion patterns in the three principal framework components (corals, coralline algae, microbialites) are studied with respect to relative light availability during coral growth and subsequent encrustation, in order to constrain the palaeobathymetry and the relative timing of the encrustation. Unexpectedly for a tropical, light-flooded setting, ichnotaxa typical for the deep-euphotic to dysphotic zone dominate. The key ichnotaxa for the shallow euphotic zone are scarce in the analysed sample set, and are restricted to the base of the deglacial succession, thus reflecting the deglacial sea-level rise. At the base of the deglacial reef succession, the ichnocoenoses present in the corals indicate shallower bathymetries than those in the encrusting microbialites. This is in agreement with radiocarbon data that indicate a time gap of more than 600 years between coral death and microbialite formation. At the top of the deglacial reef succession, in contrast, the microbioerosion patterns in the three framework components indicate a uniform palaeobathymetry, and radiocarbon ages imply that encrustation took place shortly after coral demise. An enigma arises from the fact that the ichnocoenoses imply photic conditions that appear very deep for zooxanthellate coral growth. During the deglacial sea-level rise increased nutrients and fluvial influx may have led to (seasonal?) eutrophication, condensing the photic zonation. This would have exerted stress on the coral ecosystem and played a significant role in initiating microbialite development.

Palaxius salataensis Brönnimann, Cros and Zaninetti, 1972, the oldest crustacean microcoprolite from the early Carboniferous of Guangxi, South China - Senowbari-Daryan, Baba; El Rab, Amro Gad; Heindel, Katrin; Gischler, Eberhard; Peckmann, Joern (Palaeontologische Zeitschrift, 2017)
Palaxius salataensis Brönnimann, Cros and Zaninetti, 1972, is described from early Carboniferous stromatolite mounds of a fore-reef slope setting from Laibin, Guangxi, South China. This is the oldest occurrence of internally structured crustacean coprolites. The geographic distribution and stratigraphic range of the ichnospecies as well as paleoecological implications of this new record of P. salataensis are discussed.
UnivIS-Import:2017-12-18:Pub.2017.nat.dgeo.IGM.LP.palaxi
Keywords: Carboniferous; Guangxi; Microcoprolite; Palaxius; South China

Pendant bioconstructions cemented by microbial carbonate in submerged marine caves (Holocene, SE Sicily) - Adriano, Guido; Heindel, Katrin; Birgel, Daniel; Antonietta, Rosso; Mastandrea, Adelaide; Sanfilippo, R.; Russo, Franco; Peckmann, Jörn (Palaeogeography, Palaeoclimatology, Palaeoecology, 2013)
Keywords: Autochthonous micrite; Biostalactites; Serpulids; Sicily; Submerged caves; Sulfate-reducing bacteria

Post-glacial microbialite formation in coral reefs of the Pacific, Atlantic, and Indian Oceans - Heindel, Katrin; Birgel, Daniel; Brunner, Benjamin; Thiel, Volker; Westphal, Hildegard; Gischler, Eberhard; Ziegenbalg, Simone; Cabioch, Guy; Sjövall, Peter; Peckmann, Jörn (Chemical Geology, 2012)
Keywords: Coral reef; EPS-mineralization; Fertilization; Microbial mat; Sulfate-reducing bacteria; Volcanic hinterland

Sponge-microbial build-ups from the lowermost Triassic Chanakhchi section in southern Armenia: Microfacies and stable carbon isotopes - Friesenbichler, Evelyn; Richoz, Sylvain; Baud, Aymon; Krystyn, Leopold; Sahakyan, Lilit; Vardanyan, Sargis; Peckmann, Joern; Reitner, Joachim; Heindel, Katrin (Palaeogeography, Palaeoclimatology, Palaeoecology, 2018)

Sponge Takeover from End-Permian Mass Extinction to Early Induan Time: Records in Central Iran Microbial Buildups - Baud, Aymon; Richoz, Sylvain; Brandner, Rainer; Krystyn, Leopold; Heindel, Katrin; Mohtat, Tayebeh; Mohtat-Aghai, Parvin; Horacek, Micha (Frontiers in Earth Science, 2021)
The end-Permian mass extinction was the most severe biotic crisis in Earth’s history. In its direct aftermath, microbial communities were abundant on shallow-marine shelves around the Tethys. They colonized the space left vacant after the dramatic decline of skeletal metazoans. The presence of sponges and sponge microbial bioherms has largely gone unnoticed due to the sponges’ size and the cryptic method of preservation. In addition to sponge dominated facies recently described in South Armenia and Northwestern Iran, we describe here sponge-microbial bioherms cropping out in two well-known Permian-Triassic boundary localities: the Kuh-e Hambast section, south-east of Abadeh city and the more distal Shahreza section, near Isfahan. In both sections, the extinction horizon is located at the top of an upper Changhsingian ammonoid-rich nodular limestone, called Paratirolites limestone. At Kuh-e Hambast, the overlying decimetric thick shale deposit called “boundary clay,” the latest Permian in age, is conformably overlain by well-dated transgressive basal Triassic platy limestone containing four successive levels of decimeter to meter scale, elongated to form cup-shaped mounds made of branching columnar stromatolites. Sponge fibers from possibly keratose demosponge, are widely present in the lime mudstone matrix. At the Shahreza section, above the extinction level, the boundary clay is much thicker (3 m), with thin platy limestone intervals, and contains two main levels of decimeter to meter scale mounds of digitate microbialite crossing the Permian-Triassic boundary with similar sponge fibers. Three levels rich in thrombolite domes can be seen in the overlying 20 m platy limestone of earliest Triassic age. Sponge fibers and rare spicules are present in their micritic matrix. These sponge fibers and spicules which are abundant in the latest Permian post-extinction boundary clay, followed microbial buildups during the Griesbachian time.
CRIS-Team Scopus Importer:2021-06-18
Keywords: carbonate mounds; end-permian mass extinction; Induan; keratose demosponge; metazoan bioherms

The sediment composition and predictive mapping of facies on the Propeller Mound-A cold-water coral mound (Porcupine Seabight, NE Atlantic) - Heindel, Katrin; Titschack, Jürgen; Dorschel, Boris; Huvenne, Veerle A.I.; Freiwald, André (Palaeogeography, Palaeoclimatology, Palaeoecology, 2017)
Here we provide a detailed qualitative and quantitative insight on recent sediment composition and facies distribution of a cold-water coral (CWC) mound using the example of the Propeller Mound on the Irish continental margin (Hovland Mound Province, Porcupine Seabight). Five facies types on Propeller Mound are defined: (1) living coral framework, (2) coral rubble, (3) dropstone, (4) hardground, representing the on-mound facies, and (5) hemipelagic sediment facies, which describes the off-mound area. This facies definition is based on already published video-data recorded by Remotely Operated Vehicle (ROV), photo-data of gravity cores, box cores, and dredges from sediment surfaces as well as on the composition of the sediment fraction coarser than 125 μm, which has been analyzed on five selected box cores. Sediment compositions of the living coral framework and coral rubble facies are rather similar. Both sediment types are mainly produced by corals (34 and 35 wt%, respectively), planktonic foraminifers (22 and 29 wt%, respectively), benthic foraminifers (both 7 wt%), and molluscs (21 and 10 wt%, respectively), whereas the living coral framework characteristically features additional brachiopods (6 wt%). Hardgrounds are well-lithified coral rudstones rich in coral fragments (>30 surf%), foraminifers, echinoderms, and bivalves. The dropstone facies and the hemipelagic sediment typically carry high amounts of lithoclasts (36 and 53 wt%, respectively) and planktonic foraminifers (35 and 32 wt%, respectively); however, their faunal diversity is low compared with the coral-dominated facies (12 and <2 wt% coral fragments, 7 and 6 wt% benthic foraminifers, and 4 and 0 wt% balanids). Using the maximum likelihood algorithm within ArcGIS 9.2, spatial prediction maps of the previously described mound facies are calculated over Propeller Mound and are based on mound morphology parameters, ground-truthed with the sedimentary and faunal information from box cores, photographs, and video-data. This method is tested for the first time for CWC ecosystems and provides areal estimates of the predicted facies, as well as suggests further occurrences of living coral frameworks, coral rubble, and dropstones, which are not discovered in the area yet. Thus, sediment composition analysis combined with facies prediction mapping might provide a potential new tool to estimate living CWC occurrences and sediment/facies distributions on CWC mounds, which is an important prerequisite for budget calculations and definition of marine protected areas, and which will improve our understanding of CWC mound formation.